181k views
1 vote
If you apply the changes below to the exponential parent function f(x) = 2*,what is the equation of the new function?Shift 4 units to the right.• Shift 6 units up.O A. g(x) = 2(x+6) + 4B. g(x) = 2(x– 6) + 4C. g(x) = 2(x – 4) + 6O D. g(x) = 2(x+4) + 6

1 Answer

3 votes

You need to remember the following Transformation rules for functions:

1. If


f(x+h)

The function is shifted "h" units to the left.

2. If


f(x-h)

The function is shifted "h" units to the right.

3. If


f(x)+k

The function is shifted "k" units up.

4. If


f(x)-k

The function is shifted "k" units down.

In this case you have the following Exponential parent function:


f\mleft(x\mright)=2^x

You know that it is shifted 4 units to the right and then 6 units up, then you can identify that the transformations are:


f(x-h)+k

Where


\begin{gathered} h=4 \\ k=6 \end{gathered}

Then, the equation is:


g\mleft(x\mright)=2^((x-4))+6

The answer is: Option C.

User Zied Hamdi
by
5.7k points